Detection of muscle gap by L-BIA in muscle injuries: clinical prognosis. (22nd June 2017) - Nescolarde, L; Yanguas, J; Terricabras, J; Lukaski, H; Alomar, X; Rosell-Ferrer, J; Rodas, G
Abstract: Sport-related muscle injury classifications are based basically on imaging criteria such as ultrasound (US) and magnetic resonance imaging (MRI) without consensus because of a lack of clinical prognostics for return-to-play (RTP), which is conditioned upon the severity of the injury, and this in turn with the muscle gap (muscular fibers retraction). Recently, Futbol Club Barcelona's medical department proposed a new muscle injury classification in which muscle gap plays an important role, with the drawback that it is not always possible to identify by MRI. Localized bioimpedance measurement (L-BIA) has emerged as a non-invasive technique for supporting US and MRI to quantify the disrupted soft tissue structure in injured muscles. Objective: To correlate the severity of the injury according to the gap with the RTP, through the percent of change in resistance ( R ), reactance ( Xc ) and phase-angle (PA) by L-BIA measurements in 22 muscle injuries. Main results: After grouping the data according to the muscle gap (by MRI exam), there were significant differences in R between grade 1 and grade 2f (myotendinous or myofascial muscle injury with feather-like appearance), as well as between grade 2f and grade 2g (myotendinous or myofascial muscle injury with feather and gap). The Xc and PA values decrease significantly between each grade (i.e. 1 versus 2f, 1 versus 2g and 2f versus 2g). In addition, the severity of the muscle gap adversely affected the RTP with significant differences observed between 1 and 2g as well as between 2f and 2g. Significance: These results show that L-BIA could aid MRI and US in identifying the severity of an injured muscle according to muscle gap and therefore to accurately predict the RTP.